Transgenic lettuce seedlings carrying hepatitis B virus antigen HBsAg - Marcondes, Jackson [UNESP]; Hansen, Ekkehard (Brazilian Society of Infectious Diseases, 2008)
The obtainment of transgenic edible plants carrying recombinant antigens is a desired issue in search for economic alternatives viewing vaccine production. Here we report a strategy for genetic transformation of lettuce plants (Lactuca sativa L.) using the surface antigen HBsAg of hepatitis B virus. Transgenic lettuce seedlings were obtained through the application of a regulated balance of plant growth regulators. Genetic transformation process was acquired by cocultivation of cotyledons with Agrobacterium tumefaciens harboring the recombinant plasmid. It is the first description of a lettuce Brazilian variety Vitória de Verão genetically modified.
Keywords: Edible vaccine; Hepatitis B; Oral immunization; Recombinant antigen; Transgenic plants